Inbreeding and Loss of Genetic Variation in a Reintroduced Population of Mauritius Kestrel - EWING, STEVEN R; NAGER, RUEDI G; NICOLL, MALCOLM A.C; AUMJAUD, AURELIEN; JONES, CARL G; KELLER, LUKAS F (Conservation biology, 2008)
Many populations have recovered from severe bottlenecks either naturally or through intensive conservation management. In the past, however, few conservation programs have monitored the genetic health of recovering populations. We conducted a conservation genetic assessment of a small, reintroduced population of Mauritius Kestrel ( Falco punctatus) to determine whether genetic deterioration has occurred since its reintroduction. We used pedigree analysis that partially accounted for individuals of unknown origin to document that (1) inbreeding occurred frequently (2.6% increase per generation; NeI= 18.9), (2) 25% of breeding pairs were composed of either closely or moderately related individuals, (3) genetic diversity has been lost from the population (1.6% loss per generation; NeV= 32.1) less rapidly than the corresponding increase in inbreeding, and (4) ignoring the contribution of unknown individuals to a pedigree will bias the metrics derived from that pedigree, ultimately obscuring the prevailing genetic dynamics. The rates of inbreeding and loss of genetic variation in the subpopulation of Mauritius Kestrel we examined were extreme and among the highest yet documented in a wild vertebrate population. Thus, genetic deterioration may affect this population's long-term viability. Remedial conservation strategies are needed to reduce the impact of inbreeding and loss of genetic variation in this species. We suggest that schemes to monitor genetic variation after reintroduction should be an integral component of endangered species recovery programs.